2020
DOI: 10.1016/j.ijid.2020.09.1432
|View full text |Cite
|
Sign up to set email alerts
|

Clinical management and mortality among COVID-19 cases in sub-Saharan Africa: A retrospective study from Burkina Faso and simulated case analysis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Since the outbreak of the SARS-CoV-2/COVID-19 viral pandemic, confirmed disease cases with severe complications, and especially mortality rate, have shown a strong age dependency in most countries with adequate disease reporting, showing significantly fewer severe cases in younger compared with older individuals ( Figure 1 a) [1] , [2] . Developing nations in Africa, despite reported earlier mortality, also match this pattern, such as in sub-Saharan Africa and South Africa [2] , [3] . Moreover, younger individuals appear less susceptible to infection or might lack symptoms, raising concern for epidemic asymptomatic viral spread.…”
Section: Introductionmentioning
confidence: 94%
“…Since the outbreak of the SARS-CoV-2/COVID-19 viral pandemic, confirmed disease cases with severe complications, and especially mortality rate, have shown a strong age dependency in most countries with adequate disease reporting, showing significantly fewer severe cases in younger compared with older individuals ( Figure 1 a) [1] , [2] . Developing nations in Africa, despite reported earlier mortality, also match this pattern, such as in sub-Saharan Africa and South Africa [2] , [3] . Moreover, younger individuals appear less susceptible to infection or might lack symptoms, raising concern for epidemic asymptomatic viral spread.…”
Section: Introductionmentioning
confidence: 94%
“…If effective in any group of hospitalized patients, CCP will have immense impact on health care resources and public health during this ongoing pandemic ( 74 ). CCP is rapidly available compared with other pharmaceuticals or vaccines and may be a more feasible option in surge conditions and/or resource-limited settings ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…In early case series, CCP-treated patients exhibited viral clearance and reductions in inflammatory markers ( 15 19 ). Observational studies comparing CCP-treated patients to retrospective controls showed a reduction in mortality in nonintubated patients and/or those transfused within 72 hours of hospitalization with high-titer CCP ( 20 24 ). Analysis of a subset of more than 3000 CCP recipients in an open-label study found a dose response whereby nonintubated patients who received high-titer CCP had lower mortality than those who received low-titer CCP ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Western countries, stroke ranks among the most frequent causes of non-COVID excess deaths [ 71 , 72 ], paralleled by a decrease of 39% in the number of patients asking for assistance at emergency stroke departments for acute stroke during COVID-19 [ 73 ]. In SSA countries such as Burkina Faso, many of the COVID-19 patients who died did not seek care at all, and hypertension and diabetes, main risk factors for stroke, were often reported as underlying conditions [ 74 ].…”
Section: Disruption Of Care Under Covid-19 Pandemic In Sub-saharanmentioning
confidence: 99%